Pengaruh Beban Kerja dan Burnout terhadap Kualitas Tidur Perawat dengan Usia, Jenis Kelamin, dan Pendidikan sebagai Variabel Confounding - Solehudin Solehudin; Sancka Stella; Wilda Nur Anggraini (Jurnal Siti Rufaidah, 2026)
This study aimed to analyze the influence of workload and burnout on nurses’ sleep quality while controlling for age, gender, and education as potential confounding variables. A quantitative analytic study with a cross-sectional design was conducted among 156 nurses working in a private hospital in Depok City. Data were collected using a workload questionnaire, the Maslach Burnout Inventory (MBI), and the Pittsburgh Sleep Quality Index (PSQI). The data were analyzed using Chi-Square tests and multiple logistic regression. The findings showed that both workload and burnout had significant effects on sleep quality (p < 0.05), with burnout identified as the most dominant factor. Age and gender were also significantly associated with sleep quality, whereas education did not show a statistically significant effect. The regression model demonstrated excellent fit, indicated by a McFadden pseudo R² value of 0.908. These results suggest that occupational factors, particularly burnout, play an important role in determining nurses’ sleep quality. Therefore, effective stress reduction and workload management strategies are needed to support nurses’ well-being and improve sleep quality.